Assessing the Efficacy of Differentiated Instruction for Neurodiverse Students within Inclusive Settings - Robert, Bukayo; Jordan, Inaki (Yayasan Gema Bina Nusantara, 2026)
This research assesses the efficacy of Differentiated Instruction (DI) as a pedagogical framework for supporting neurodiverse learners within inclusive general education settings. As classrooms become increasingly diverse, the traditional